(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The pervious concrete framework and its comparing quality are as critical as its penetrability characteristics. The quality of the framework not as it were depending on the compressive quality of the pervious concrete but moreover on the quality of the soil underneath it for bolster. Previous studies have shown that permeable concrete has lower compressive strength than conventional concrete and can only withstand light truck loads. This project was an experiment to examine the compressive strength of permeable concrete as it relates to the water-cement ratio, aggregate ratio, aggregate size and degree of compaction. To enhance the strength and permeability of concrete, it is crucial to strike a balance between the water-cement ratio and the presence of voids. By optimizing the proportions of water, cement, and aggregates, the goal is to minimize voids without compromising the overall strength of the concrete. This delicate equilibrium ensures improved durability and resistance while allowing for adequate permeability to water and other substances. The aim is to achieve a cohesive and robust concrete mixture that meets both structural and functional requirements.. Pervious concrete pavement is unique and effective means to meet growing environmental demands, by landing rainwater and allowing it to seep into the ground.